IMPULSE RESPONSE FUNCTION ANALYSIS OF UNEMPLOYMENT RATE, INFLATION, POVERTY AND ECONOMIC GROWTH IN INDONESIA - Cut Putri Mellita Sari; Rasyimah Rasyimah (Journal of Malikussaleh Public Economics, 2021)
The purpose of this study is to analyze how the shock or impulse response function of the variables of the unemployment rate, inflation and poverty rate on economic growth within the research period from 1998-2020. The method used is the Impulse Response Function (IRF) through the Vector Error Correction Model (VECM) approach. The results prove that the response given by the unemployment rate (UN) to economic growth due to shocks show a positive response up to the 8th period. The most influential variable on economic growth (PE) is the unemployment rate (UN). Therefore, it is suggestted for the government to provide adequate jobs (as needed) so as to reduce the relatively high unemployment rate and will have an impact on increasing poverty rates in Indonesia.